Visible Minorities and Job Mobility: Evidence from a Workplace Panel Survey - Mohsen Javdani (Institute of Labor Economics (IZA), 2019)
In this study we use Canadian linked employer-employee data to examine whether visible minority Canadian-borns experience any differences in their inter-firm and intra-firm job mobility, as well as wage returns associated with them, compared to white Canadian-borns. We also examine the extent to which any differences in intra-firm mobility operates within firms versus between firms. Our results suggest that both male and female visible minority Canadian-borns experience substantial differences in probability of promotion, number of times promoted, and wage returns to promotions, compared to their white peers. For male visible minorities, these differences with their white peers mainly operate within firms. For female visible minorities however, almost half of the gap is driven by their crowding into firms with fewer promotion opportunities. In terms of inter-firm mobility, while male visible minorities are similarly likely to move between firms compared to their white peers, female visible minorities are less likely to change employer. Both groups however receive similar wage returns to their inter-firm mobility. This seems to suggest that differences in intra-firm mobility do not translate into visible minorities moving more frequently between firms, or receiving higher returns to their inter-firm mobility. We find no evidence that these differences could be driven by differences in hierarchical level, career path, or immigration background. Labour market discrimination however remains a potential contributor to these differences, which is also consistent with some of our findings. Our results also suggest that for female visible minorities, different family responsibilities driven potentially by different cultural norms or family dynamics could also contribute to these differences.
Keywords: J15; J62; J71; M51; 330; promotions; inter-firm mobility; job mobility; visible minority; ethnic minority; discrimination